The Sheep as an Animal Model in Orthopaedic Research - Potes, J.C. (2009)
The use of sheep as model in remodeling process in cancelous and cortical bone for the assessment of new orthopaedic biomaterials and implants, in biomechanical studies and as model for tissue-engineered bone constructs has been described in the literature. Sheep are a well accepted model for in vivo studies in orthopaedic research to address the biomechanical, biochemical and histological processes of bone biology, due to similarities with humans in weight, size, bone and joint structure and bone remodeling process. This paper describes a technical sequence of procedures, including anaesthesia and surgery steps, using as standard surgical procedures in the sheep as an experimental model to evaluate the mechanical behaviour of new concepts of hip implant, rapidly manufactured in the surgery time, and to study the osteointegration phenomenon through histological analysis.